The global effects of US fiscal policy - Kimberly Flood (Bank of Canada, 2008)
The author examines the global impact of U.S. fiscal policy using the Bank of Canadas' Global Economy Model (Lalonde and Muir 2007). In particular, she examines the global macroeconomic implications of the expiration of major tax cuts in the United States and of expected increases in U.S. entitlement program expenditures. The results of her analysis suggest that the expiration of previously enacted tax cuts in the United States will impose short-run costs on the U.S. economy. However, the rest of the world will benefit from an associated decline in the world real interest rate and from a redistribution of wealth linked to a partial reversal of global current account imbalances as U.S. government debt declines. The authors' analysis of the expected increase in U.S. entitlement program expenditures, financed through debt, suggests that entitlement program expenditures will crowd out economic growth in the United States and the rest of the world.
Keywords: H0; H2; H3; 330; Fiscal policy; International topics; Regional economic developments; Finanzpolitik; Steuersenkung; Öffentliche Ausgaben; Weltwirtschaft; Wirkungsanalyse; USA; Welt